Territorial Indicative Budget Ceilings (PIK) as Instrument of Technocracy of Regional Development Planning - Sarjiyanto, Sarjiyanto; Mulyadi, Mulyadi (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
This research aims at analyzing the local government policy related to the local budget posture in the each territorial. There are uncertainty methods in dividing and formulating the local budget posture in each territorial in Indonesia. It is not depend on the actual economic variables of each territorial. This study uses the literature studies to collect the data of planning and budgeting. The content analysis of this local government economic policy is based on of the planning and budgeting process itself. The detailed information is found by observations and in-depth interview with the informants about the planning and budgeting process in Rembang. The result shows the variables that can determine the fair instrument in formulating the local budget posture some of which are: the number of population, the number of drop out (DO), the illiteracy (IR), the infant mortality rate (IMR), the malnutrition data, the number of poor (HCI), the economic growth, the damaged road infrastructure, the damaged irrigation system, the damaged schools, the land building tax, and the amount of retribution.